STRONTIUM ISOTOPE VARIATIONS IN LOWER TERTIARY-QUATERNARY VOLCANIC ROCKS FROM THE KURILE ISLAND ARC - Frolova T.I.; Bailey J.C.; Larsen O. (My University, 1987)
Average 87Sr/86Sr ratios for lavas from Quaternary and Pleistocene volcanoes of the Kurile island arc, NW Pacific, decrease from 0.7035 in the south to 0.7032 in the north. The northern Kuriles are characterised by K2Oricher volcanics and by an older crust. Varying ratios show no simple relation to crustal thickness or geochemical indicators of crustal contamination. This is thought to reflect the immature character of the crust — its simatic composition, low Rb/Sr ratios and youthfulness. Older lavas from the Kuriles (Lower Tertiary, Miocene) have similar or slightly higher 87Sr/86Sr ratios; some have suffered slight alteration and possibly crustal contamination. Quaternary volcanics from the Kurile and Aleutian arcs have the lowest 87Sr/86Sr ratios of all circum-Pacific arcs and this may be ascribed to (a) the isotopic individuality of the landward North American plate and/or (b) the high degree of mechanical coupling between the Pacific and North American plates reducing the amount of subducted 87Sr-rich sediments and seawater. An isotopic boundary between island arcs is located in central Hokkaido. The primary basaltic magmas of the Kuriles were derived from mantle recently contaminated by radiogenic Sr. Subsequent fractionation to andesites and dacites occurred by closed-system fractional crystallization.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная